What Is ‘Old’ in Old Age? An Inquiry into Swahili Paremia - Ahmad Kipacha (Nordic Journal of African Studies)
This article is about gerontological proverbs in Swahili folkloric discourses. The question posed in this study is as follows: how is old age depicted according to Swahili paremiology? To answer this question, 49 popular Swahili gerontological proverbs have been analysed. The findings show that Swahili gerontological proverbs, like other non-Western gerontological proverbs, pay due respect to elders who are considered wise, knowledgeable, and experienced. How someone is perceived to be an elder is largely socially and culturally constructed. There are several Swahili gerontological proverbs that are equivalent to proverbs in different cultures and languages including Russian, German, Yiddish, French, Chinese, Arabic, and others.